Fabrication of silver nanoparticles using Arnebia hispidissima (Lehm.) A. DC. root extract and unravelling their potential biomedical applications - Shruti Nindawat; Veena Agrawal (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
The present study reports the biosynthesis of silver nanoparticles using aqueous root extract of Arnebia hispidissima. They were prepared by adding 10 mL root extract in 90 mL silver nitrate (0.5 mM) solution and heating at 60 ± 2 °C for 12 min at pH 7.5. Characterization of the biosynthesized silver nanoparticles was done using UV-Visible spectroscopy, field emission scanning electron microscopy, energy dispersive X-ray analysis, transmission electron microscopy, X-ray diffraction analysis, dynamic light scattering measurements and Fourier-transform infrared spectroscopy. The synthesized silver nanoparticles were crystalline in nature exhibiting different shapes like sphere, rod, triangle, hexagon and polygon. Their zeta potential was −23.6 mV confirming their high stability. Fourier-transform infrared spectroscopy analysis showed the presence of phenolics, flavonoids and proteins as reducing, capping and stabilizing agents. The synthesized nanoparticles showed effective in vitro anti-oxidant activity against DPPH (IC50 = 9.86 µg/mL) and H2O2 (IC50 = 53.78 µg/mL) radicals. The nanoparticles showed dose-dependent cytotoxicity against HeLa (cervical cancer, IC50 = 4.44 µg/mL) cells and were non-toxic towards normal L20 B cells (non-malignant mouse cell line). They also exhibited strong anti-microbial activity against Candida albicans, Candida tropicalis, Geotrichum candidum (fungal strains); Escherichia coli, Staphylococcus aureus, Enterococcus faecalis, Klebsiella pneumoniae (bacterial strains). This is the first report of synthesis of silver nanoparticles using A. hispidissima root extract validating their bioefficacy against HeLa cancer cells and diverse microorganisms.